As it is in Heaven (Journal of Parents and Teachers, 2018)
After suffering a heart attack at his career prime, the protagonist, Daniel Daréus, a renowned conductor, decides to move to his hometown, located in an isolated area of northern Sweden, where the most tacit traditions prevail of the Lutheran church, to have shelter in the peaceful environment that he longs for, as well as to recall his experiences of childhood. Despite his quiet lifestyle, his presence has aroused great curiosity, confusion and fascination. However, his life will take a new direction by accepting the request made by the group of neighbors that make up the choir of the church and willing to learn their masterful skills. The talent, professionalism and charisma of Daniel will make him accept the attractive offer and resume his art capable of humanizing those people with his genuine passion, that is, the music in all its essence, getting the best of each one of them. Also, the protagonist will overcome their fears and life in solitude.
Keywords: cinema and choral music; cinematographic and educational guide; school harassment; gender violence; communication; empowerment; respect; tolerance